El valor vinculante de la jurisprudencia en el sistema de fuentes y la jurisprudencia de la corte interamericana de derechos humanos en el derecho interno de los países miembros de la convención (2019)
The following article is written in prose form, summarizing some of the theses and theories raised regarding the binding value of the jurisprudence of the IACHR, as a source of law, a study conducted at jurisprudence and doctrine level, dividing it into two thematic pillars Which are 1. Binding value of jurisprudence at the domestic level and 2. Binding force of the IACHR rulingsin domestic law.